2009
DOI: 10.2478/v10078-09-0001-x
|View full text |Cite
|
Sign up to set email alerts
|

Sensation Seeking and Spatial Ability in Athletes: an Evolutionary Account

Abstract: The aim of this study was threefold: (a) to examine sex differences in sensation seeking and spatial abilities in a sample of athlete students, (b) to explore whether measures of sensation seeking and spatial ability can be used to distinguish between athletes engaging in sports of different levels of risk, and (c) to explore the relationship between sensation seeking and spatial abilities in a sample of athlete students. A total of 201 students athletes engaged in sports of different levels of risk completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
2
2
0
Order By: Relevance
“…The significance of this factor was also confirmed by the distribution of sten scores: almost 70% of the women in the study received high scores. These results are consistent with the findings of Hromatko and Butković [22], who found intergender differences in sensation seeking. Men were characterised by higher scores in disinhibition, while women were characterised by higher scores in experience seeking.…”
Section: Discussionsupporting
confidence: 93%
“…The significance of this factor was also confirmed by the distribution of sten scores: almost 70% of the women in the study received high scores. These results are consistent with the findings of Hromatko and Butković [22], who found intergender differences in sensation seeking. Men were characterised by higher scores in disinhibition, while women were characterised by higher scores in experience seeking.…”
Section: Discussionsupporting
confidence: 93%
“…Girls may have denied both practice and perceptual sense of SS activities due to family and social pressures or lack of tolerance. This result of our study is consistent with the results of the studies which concluded that males are higher than women in SS level [25][26][27]. In a study interests and preferences of SS, Buswell and James [28] examined 332 students of a university who were majoring in health, physical education, recreation and elementary education; the results referred to significantly higher scores for males in SS.…”
Section: Male-female Comparisons For Ss and Lcsupporting
confidence: 91%
“…7 In the other studies that performed in three categories of sports, males had better spatial ability on average compared to females in all categories.However, there are different significances on each category. 11 There are significant differences between low risk sports activity (running, athletics, and gymnastic) and high risk sports activity (parachuting, scuba diving, skiing, and mountain climbing), while on moderate risk sports activity (football, basketball, and handball), there is no significant difference.…”
Section: -11mentioning
confidence: 98%
“…Several studies had reported differences and other studies had reported no differences at all. 8,[10][11] However, it is not known whether occupation or daily activities influence spatial ability, such as what is happened to in athletes.…”
Section: Introductionmentioning
confidence: 99%